Why do you adopt social networking sites? Investigating the driving factors through structural equation modelling - Jan, Muhammad Tahir (Emerald Group Publishing Ltd., 2017)
Purpose – The purpose of this paper is to investigate those factors that are associated with the adoption of social networking sites from the perspective of Muslimusers residing in Malaysia. Design/methodology/approach – A complete self-administered questionnaire was collected from 223 Muslim users of social networking sites in Malaysia. Both exploratory and confirmatory factor analyses were used to sort the significant items for the constructs and to check the validity. Structural equation modelling was applied in testing the hypotheses and the fitness of the proposed model. Findings – The results of full structural model attest that technological and social factors are the most significant factors behind the adoption of social networking sites. However, this is followed by an educational factor. Among Muslim users in Malaysia, the study does not find significant influence of brand or product communication behind this adoption. Originality/value – The paper investigates those factors that are considered inevitable in the adoption of social networking sites. Invaluable findings were offered in the form of a structural model for the stakeholders of social networking sties. These findings can be used in planning and making decisions that may benefit all parties associated with it.